2011
DOI: 10.1111/j.1365-2966.2011.20135.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the local density in shaping the galaxy stellar mass functions★

Abstract: Exploiting the capabilities of four different surveys – the Padova–Millennium Galaxy and Group Catalogue (PM2GC), the WIde‐field Nearby Galaxy‐cluster Survey (WINGS), the IMACS (Inamori‐Magellan Areal Camera and Spectrograph) Cluster Building Survey (ICBS) and the ESO (European Southern Observatory) Distant Cluster Survey (EDisCS) – we analyse the galaxy stellar mass distribution as a function of local density in mass‐limited samples, in the field and in clusters from low () to high () redshift. We find that a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 58 publications
11
73
3
Order By: Relevance
“…The values of the projected local density that we use are calculated from a circular area enclosing the first 10 most nearby galaxies, which also accounts for background counts as expected from Berta et al (2006) and is corrected for border effect (see Vulcani et al 2012, for details). The local density is expressed as the logarithm of the number of galaxies with M V ≤ −19.5 per Mpc −2 .…”
Section: Emission-line Galaxies In Local Clustersmentioning
confidence: 99%
“…The values of the projected local density that we use are calculated from a circular area enclosing the first 10 most nearby galaxies, which also accounts for background counts as expected from Berta et al (2006) and is corrected for border effect (see Vulcani et al 2012, for details). The local density is expressed as the logarithm of the number of galaxies with M V ≤ −19.5 per Mpc −2 .…”
Section: Emission-line Galaxies In Local Clustersmentioning
confidence: 99%
“…In Vulcani et al (2012), we analysed specifically the dependence of the mass function on local density, using collectively the WINGS, PM2GC, ICBS, and EDisCS samples. We found that both in the local and distant universe, in clusters and in the field, local density plays an important role in driving the mass distribution.…”
Section: Global and Local Environmentmentioning
confidence: 99%
“…Some studies have attempted to measure the SMF as a function of local environment at 0.4 z 1.2 (e.g. Bundy et al 2006;Bolzonella et al 2010;Vulcani et al 2011Vulcani et al , 2012Giodini et al 2012). A measurement of the SMF at the highest densities has not yet been achieved in this redshift range.…”
Section: Introductionmentioning
confidence: 99%